Foundations of Education in Nepal: Local Values in School Governance Practices - Adhikari, Devendra (NPRC Journal of Multidisciplinary Research, 2025)
School Governance in Nepal is largely discussed through the policy perspectives, without identifying its fundamentalism. Existing research also attributes poor school governance for deteriorating educational quality; however, these studies have presented inconclusive findings on how and what exactly needs to be strengthened in school governance. I argue that social-cultural domains have shaped the school governance in the country for years and deserve further exploration. In this research, I explore how peoples’ local values constitute Nepali school governance through localism-governance theoretical lens. I applied a narrative research methodology and interviewed school stakeholders including School Head teachers, teachers, Education officers, parents, and SMC members in Lalitpur, Nepal. I found that local values provide a strong sociological foundation for school governance. These guiding norms include the community legacy that motivates the establishment and management of schools, a culture of care, and the value of belonging among school stakeholders. Such cultural orientations have played a significant role in shaping public school governance in Nepal and should be meaningfully integrated in the education policy debates. Although this study focuses on Lalitpur district, Nepal, its findings can be useful for educational policy makers and academics both within Nepal and beyond.